Testing the easterlin paradox: Results and policy implications - Beja, Edsel L, Jr (Archīum Ateneo, 2018)
The Easterlin Paradox is about the contradiction between an evidence of a short-run relationship between happiness and income growth and no evidence of a long-run relationship between happiness and income growth. The paper argues that there is confirmation of the Easterlin Paradox when the magnitude of the estimated long-run relationship is practically equal to zero notwithstanding its statistical significance. The findings of the paper support the Easterlin Paradox.